Xantphos Doped POPs‐PPh3 as Heterogeneous Ligand for Cobalt‐Catalyzed Highly Regio‐ and Stereoselective Hydrosilylation of Alkynes. Issue 1 (28th November 2018) - Li, Ren‐Hao; Zhang, Guo‐Liang; Dong, Jia‐Xing; Li, Ding‐Chang; Yang, Ying; Pan, Ying‐Ming; Tang, Hai‐Tao; Chen, Li; Zhan, Zhuang‐Ping
Abstract: A Co(acac)2 /POL‐Xantphos@10PPh3 ‐catalyzed hydrosilylation of unsymmetrical internal alkynes with Ph2 SiH2 has been developed for the synthesis of highly selective syn ‐α‐vinylsilane products. Furthermore, terminal alkynes were also used and gave the products with excellent regioselectivity and a wide functional group tolerance. Because this porous organic polymer combines the selectivity and activity merits of Xantphos with the stability advantage derived from the high concentration of PPh3, the Co(acac)2 /POL‐Xantphos@10PPh3 can be recycled multiple times without loss of activity and selectivity. This heterogeneous catalyst is expected to find promising applications in industrial synthesis. Abstract : Porous organic polymer : A Co(acac)2 /POL‐Xantphos@10PPh3 ‐catalyzed hydrosilylation of unsymmetrical internal alkynes with Ph2 SiH2 has been developed for the synthesis of highly selective syn ‐α‐vinylsilane products. Furthermore, terminal alkynes were also used and gave the products with excellent regioselectivity and a wide functional group tolerance.